Spatiotemporal Dynamics and Trade-Off Analysis of Ecosystem Services in the Caijiachuan Watershed of the Loess Plateau - Guiyun Song; Tianxing Wei; Qingke Zhu; Huaxing Bi; Jilong Qiu; Junkai Zhang (Agronomy)
As a typical reforested region of the Loess Plateau, the Caijiachuan watershed plays a vital role in ecological security and resource management. This study evaluates the spatiotemporal variations in key ecosystem services—namely soil retention, water yield, carbon storage, and habitat quality—between 2002 and 2024 using the InVEST model, calibrated with field-measured rainfall, carbon density, and high-resolution land use data derived from integrated remote sensing and field surveys. Statistical analyses based on the R language reveal dynamic trade-offs and synergies among these services. The results show that: (1) soil retention, carbon storage, and habitat quality have steadily improved, while water yield shows an overall upward trend with significant spatial heterogeneity; (2) a consistent and significant trade-off exists between carbon storage and water yield (average R2 ≈ 0.28), while other ecosystem service interactions are relatively weak; (3) climatic variability, topographic heterogeneity (e.g., slope and elevation), and vegetation structure are key drivers of these trade-offs. This study provides scientific evidence to support ecological management and policy formulation in reforested areas of the Loess Plateau.